KAJIAN BATAS PENGARUH KOTA TERHADAP WILAYAH SEKITARNYA (STUDI KASUS: KOTA MANADO, KOTA BITUNG, KOTA TOMOHON, DAN KOTA KOTAMOBAGU) - Anna Maria Watung Supit; O. Esry H. Laoh; Melissa L. G. Tarore (AGRI-SOSIOEKONOMI, 2018)
This study aims to find out how far the limits of city influence on the surrounding area (case study: Manado City, Bitung City, Tomohon City, and Kotamobagu City). The data used in this research is secondary data. The variables measured in this study include population (soul) and distance (km). In this research the analysis used is Breaking Point. The study took place from October to April starting from preparation, data collection, to the production of research results. The location of the research was conducted in Manado City. The results showed that the development of City Region (BWK) of Manado City, Bitung, Tomohon, and Kotamobagu, has different influence limits. BWK Manado City Center has a stronger boundary of influence over Airmadidi, Tondano Utara, Bitung and Amurang areas. BWK Bitung City Center has stronger limits of influence, especially on Kauditan and Airmadidi areas. While the area of Manado has lower influence limits. The limits of influence of BWK Tomohon City Center have a stronger boundary effect on North Tondano and Sonder areas. While the area of Manado has lower influence limits. Similarly, the Influence Limits of BWK Kotamobagu City Center has a stronger influence limit on the Amurang and Tutuyan areas. Then the relationship of the four cities shows that Manado City has more influence than Bitung, Tomohon and Kotamobagu.